Pay attention to Surat Yusuf  (Journal of the College of Basic Education, 2022)
The research plan included three sections and a conclusion in which it reached the most prominent results.The first topic dealt with paying attention to pronouns in Surat Yusuf (peace be upon him), as well as paying attention to the speaker's pronoun to backbiting and paying attention to the rest of the other pronouns. While the second topic dealt with: paying attention to verbs, from the present tense to the past and vice versa, and also the transition from the imperative verb to the past tense. And the third and last topic was entitled (Passing in the Context of the Sentence), in which I dealt with turning around in sentences, including turning from the actual sentence to the nominal sentence and vice versa.